Kemandekan Gerakan Mahasiswa di Era 4.0: Studi Kasus Ikatan Mahasiswa Muhammadiyah Kota Semarang - M. Ragil Yoga Priyangga; Wijayanto - -; Laila Khalid Alfirdaus (Journal of Politic and Government Studies, 2021)
Since the Covid-19 pandemic, IMM (Muhammadiyah Student Association) Semarang city has stagnated its online movement. Why did this happen? This is the research question. This study uses a qualitative approach and a constructivist paradigm, while the data is obtained through personal experience tracing, in-depth interviews, and documents. This study found three causes for the stagnation of the movement: first, there was a branch of Hikmah that emerged as the ruler of a fractured discourse since the beginning of the leadership. Unfortunately, the rift has been solidified through a disciplinary process. This is done in two ways, namely by implementing the regulation "myth of representation" and normalizing the annulment of votes suspected of conducting counter-discourse or resistance. Second, the stuttering of IMM Semarang City in building a movement in the digital era and pandemic. Third, the ineffectiveness and non-optimal movement. This is indicated by the discourse that the cadres fail to accept, and the misalignment of tastes between the narratives produced and what the cadres are interested in. There are two alternative ways to overcome the stagnant movement of this movement, namely: the need for action to understand today's consumption mindset and apply a popular approach to rebuild the public sphere. With that, this research can be a material for reflection and organizing experimentation for each movement actor.